TAMEx framework as an alternative for e-exam implementation in wireless network - Gede Sukadarmika; Rukmi Sari Hartati; Linawati Linawati; Nyoman Putra Sastra (Universitas Ahmad Dahlan, 2020)
One of significant change in learning process is exam implementation applying a computer-based test (e-exam) rather than paper-based test. Many institutions currently use wireless network with bring your own device (BYOD) policy for their e-exam implementation, due to limitation of space and user terminals. Moreover it is hard to maintain the availability of reliable signal quality in wireless network for all users during e-exam process. Therefore, this research proposes a development of time adaptive for mobile exam (TAMEx) framework to provide all users with good quality of service of e-exam in wireless network environment when dealing with signal quality variations. The received signal strength indication (RSSI) is the main indicator of the signal quality. The framework supports e-exam implementation in wirelesslocal area network and the use of BYOD mechanism. The research shows that the framework successfully has provided time compensation for the users who experienced temporary connection loss due to bad signal quality. The result exhibits that tiny processing time has been needed for signal loss detection, user’s request of compensation time, and server’s execution. In conclusion, the TAMEx could guarantee good services for all users who doing e-exam in wireless network environment.